Faktor-Faktor yang Mempengaruhi Kualitas Informasi Laporan Keuangan Pemerintah Daerah Kota Batam - Dwitania Putri, Raja Hamizah; Hasanah, Afriyanti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research aims to test factors that can affect the quality of information in local government financial statements or LKPD of Batam City. Independent variables in this research are competencies, regulation, and politics. This research used questionnaire data from Head of Finance of Satuan Kerja Perangkat Daerah or SKPD in Batam City with a total of 44 respondents. This research used multiple linear regression analysis with SPSS application. This research found that partially, the quality of information in LKPD can be influenced by competencies and regulations but not by politics. Moreover, simultaneously, competencies, regulation, and politics affect the quality of information in LKPD by contributing 67.9% of influence on LKPD.